A comparative study of life cycle carbon emissions and embodied energy between sun-dried bricks and fired clay bricks. (1st December 2020) - Dabaieh, Marwa; Heinonen, Jukka; El-Mahdy, Deena; Hassan, Dalya M.
Abstract: This study presents a comparison of the life cycle carbon emission (LCCO2 ) and embodied energy calculation between two kinds of bricks, sun-dried and fired clay, as means of evaluating the energy and climate impact of each brick type and the economics of production. Focus is paid to the differences across the whole production chain between sun-dried clay bricks, which represent the traditional norm, and fired clay bricks, which are the most widely-used walling materials in conventional buildings. A case study was carried out in Dakhla Oasis in the Western Desert of Egypt. The results of this study show that if sun-dried bricks are used instead of fired bricks, a reduction of up to 5907 kg CO₂e (in CO₂ emissions) and 5305 MJ of embodied energy for every1000 bricks produced could be achieved. The paper concludes by offering alternative scenarios for brick-making and suggestions for improving sun-dried brick production. The methodology used in this study contributes to the development of an investigative-comparative way to assess choices between building materials. It also intends to help inform local homeowners and building practitioners not only in Egypt, but also globally, about resource depletion, energy consumption, and harmful emissions from fired industrial bricks as a common building construction material. Highlights: Sun dried clay bricks are a nearly zero carbon building material with low embodied energy. For every 1000 sun-dried bricks, a reduction in CO₂ by 5907 kg CO2e and 5305 MJ EE is achieved. Social and cultural norms can affect the choice of different building materials.